The neural representation of absolute direction during mental navigation in conceptual spaces - Simone Viganò (Nature Portfolio, 2021)
Viganò et al. use fMRI in healthy human participants to show that conceptual navigation elicits a spatial code for absolute direction in the medial parietal cortex. Their findings are suggestive of a complementary mechanism for conceptual navigation outside the hippocampal formation.